2022
DOI: 10.3390/ph15101212
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Effects of Saudi Sumra Honey against Drug Resistant Pathogens: Phytochemical Analysis, Antibiofilm, Anti-Quorum Sensing, and Antioxidant Activities

Abstract: Honey exhibited potential antimicrobial activity against multidrug resistant (MDR) bacteria that continues to be a serious health problem. We reported the in-vitro activity of Saudi Sumra honey against clinical pathogenic bacteria and fungi, antibiofilm, anti-quorum-sensing (QS) and antioxidant activities in relation to its phytochemical composition assessed by gas chromatography-mass spectrometry (GC-MS). Broth dilution method and scavenging activities against 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…In addition, honey contributes to absorbing wound exudate, initiating the exfoliation of wounds, and keeping the wound area moist [ 32 ]. Furthermore, it has been documented that honey can inhibit the QS system of bacterial communities [ 33 , 34 , 35 ]. Recent experiments have indicated that honey could become an effective alternative, even in the elimination of antibiotic-resistant bacteria, including wound-infecting bacteria [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, honey contributes to absorbing wound exudate, initiating the exfoliation of wounds, and keeping the wound area moist [ 32 ]. Furthermore, it has been documented that honey can inhibit the QS system of bacterial communities [ 33 , 34 , 35 ]. Recent experiments have indicated that honey could become an effective alternative, even in the elimination of antibiotic-resistant bacteria, including wound-infecting bacteria [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…New methods widely explored phytochemicals extracted from natural sources to prevent biofilm formation and quorum-sensing. 174 , 175 Phytochemicals, alone or in combination, have been used to repurpose old antibiotics or reduce the dose of antibiotics. 176 , 177 Human cultures have been using herbal remedies for centuries, and some of these natural products are useful in treatment and prevention.…”
Section: Innovative Approaches To Curb Biofilm Formationmentioning
confidence: 99%
“…To generate data with decent reliability and reproducibility for practical comparison, reference Gram-positive and negative bacterial strains were purchased from the American Type Culture Collection (ATCC) (Manassas, United Sumra and Sider honey was obtained from an authenticated company that sold honey in Al-Bah city, Saudi Arabia (Al Amari, AL-Baha, Saudi Arabia). 17 In addition, medical grade Manuka honey (Methylglyoxal 400) was purchased from MaunukaGuard (Monterey, California, USA), 9 which was utilized as a positive control. All of the obtained honey was inoculated into MHA plates and incubated at 37°C for 24 hours to ensure the absence of any contamination (a purity check), then prepared as a 90% stock solution using sterile distilled water (dH 2 O) before any experimental work was conducted.…”
Section: Collection Of Bacterial Isolates Honey Samples and Antibioti...mentioning
confidence: 99%
“…Moreover, Saudi Sumra honey has been proven to be effective against multidrug-resistant (MDR) S. aureus, E. coli, and Candida albicans in single and/or polymicrobial cultures. 17 Although the above-mentioned studies have highlighted the promising activity of Saudi honey and its historical usage in traditional medicine to treat infectious diseases, there is a clear research gap concerning the effect of the prolonged, repeated in-vitro exposure of Saudi honey on bacterial resistance to conventional antibiotics, as well as its ability to create biofilm. This in-vitro study is essential for any potential therapeutic use of Saudi honey to treat infections caused by MDR and biofilmforming pathogenic bacteria.…”
Section: Introductionmentioning
confidence: 99%